Social Fashion: exercises of method - Terracciano, Bianca (E|C, 2020)
Ten years later the advent of social networks and social fashion, may we conceive a scientific methodology of analysis dedicated to such problems? The answer is obviously yes: in this paper I will propose a path which includes the fundamental stages of the generation and application of a specific tool. I will apply a multidisciplinary qualitative method, based on the semiotic theory, that seems appropriate to investigate analytical objects concerning social networks, beyond fashion.